Dampak Pandemi COVID-19 Terhadap Harga Saham Syariah di Indonesia - Yunianto, Bobby Verdi; Bahruddin, Yusra Muhammad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Since march 2020, COVID-19 pandemic has had several direct impacts on Indonesia, This led to a decrease in the value of each sector; In particular, the financial sector remains unaffected by the pandemic. COVID-19 is the main cause of this decline; This led to a decrease in the value of ICI in all sectors on the stock exchange. However, other sectors are helping to outlast others during the pandemic. Banking and financial institutions produce many successful sectors. This can be seen in the banking and financial industry, which is home to BRIS and BBTN. The purpose of this study is to consider the life of BRIS stocks during the pandemic. This will be done by analyzing how the public responds to Islamic stock investment during the PSBB social movement. From March to December, data was collected through qualitative methods because it came from Investing.com and the Indonesia Stock Exchange IDX. This is because of the lockdown that has been implemented so far. The results of this study show that BRIS and BBTN stocks can survive and increase stock prices highly during the COVID-19 Pandemic.